A Rare Complication of Cardiac Ablation: Atrial-esophageal Fistula Presenting as Odynophagia - Khan, Muzammil (Cureus, 2020)
Radiofrequency catheter ablation has been commonly used for the treatment of drug-refractory atrial fibrillation. The esophageal injury along with the development of atrial-esophageal fistula (AE fistula) is fairly rare but is a devastating complication of catheter ablation. Described in 2004 for the first time, it is the most lethal of all the complications of catheter ablation with a high mortality rate. The clinical presentation of an AE fistula is variable, however, early diagnosis and treatment can prevent a fatality. We have reported a case of an AE fistula post catheter ablation for drug-resistant atrial fibrillation, along with its treatment, diagnosis, and possible preventive measures.